DYNAMICS OF IMPLEMENTATION OF MODERN IRRIGATION TECHNOLOGIES IN SAMARKAND REGION - Namozov Jurabek Abduazizovich; Khamroeva Feruza Asrorovna (Journals Park Publishing, 2022)
There are constant changes in the structure of agricultural industries. One such change is the processes associated with irrigation systems. The article talks about modern irrigation methods implemented in the region, including drip irrigation. The change of these processes in 2008-2018 was scientifically analyzed and tabulated. The data is presented in two different charts for better understanding. In the concluding part of the work, proposals and recommendations on the implementation of drip irrigation in the region are given.
Keywords: modern irrigation technologies, water resources, drip irrigation, Samarkand region, districts